2023
DOI: 10.3389/fpubh.2023.1293875
|View full text |Cite
|
Sign up to set email alerts
|

Improving child nutrition in disasters by developing a modeled disaster preparedness nutrition education curriculum

Akindele Abimibayo Adeoya,
Shinichi Egawa,
Adebayo Sunday Adeoya
et al.

Abstract: In contemporary global society, largely because of climate change and other natural and human-induced hazards, disasters are an almost daily occurrence. The nutritional impact of disasters on children results in long-term physical and mental health problems. As children are one of the most vulnerable demographic groups, they must be empowered with disaster preparedness nutrition knowledge, and the skills and motivation to survive, prevent/reduce malnutrition, and maintain good health during disasters. A disast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In a relevant study, Hirase and colleagues suggested practical solutions like the use of plates 3 and wristbands with informative signage and good visibility to address the dietary needs of children with food allergies. Additionally, 4 developed a disaster preparedness nutrition education curriculum to empower children, including those with food allergies, with practical skills and knowledge to navigate nutritional challenges and enhance preparedness. These program and tools can raise awareness and effectively communicate dietary restrictions and allergenic triggers, ensuring these children receive necessary support, even in everyday situations and during disasters.…”
mentioning
confidence: 99%
“…In a relevant study, Hirase and colleagues suggested practical solutions like the use of plates 3 and wristbands with informative signage and good visibility to address the dietary needs of children with food allergies. Additionally, 4 developed a disaster preparedness nutrition education curriculum to empower children, including those with food allergies, with practical skills and knowledge to navigate nutritional challenges and enhance preparedness. These program and tools can raise awareness and effectively communicate dietary restrictions and allergenic triggers, ensuring these children receive necessary support, even in everyday situations and during disasters.…”
mentioning
confidence: 99%